Rabdomiosarkoma - Helmi Ismunandar; Rani Himayani; Diki Prawira Adifa (Medula, 2021)
Rhabdomyosarcoma is a soft tissue malignancy with prevalences about 5% of all malignancies in children and 20% of soft tissue malignancies that occur in children. The most common primary tumor sites include the head and neck area followed by the genitourinary and extremities. Meanwhile, the most common subtypes are embryonic in children and alveolar in adolescents. Although the specific etiology for RMS is largely unknown, there are increased risk factors for environmental factors such as radiation and drugs, syndromes, and chromosomal abnormalities. The clinical symptoms vary and are related to the location of the mass and the blockage it caused. Histopathological and immunohistochemical examinations are gold standard tests for diagnosing RMS and determining subtypes that serve as prognosis and therapy. Various therapeutic approaches can be surgery, chemotherapy, radiotherapy, or in a combination.